Cui bono - business or labour? job retention policies during the Covid-19 pandemic in Europe - Ebbinghaus, B; Lehner, L (SAGE Publications, 2022)
Europe faces multiple challenges during the Covid-19 pandemic, including the problem of how to secure jobs and earnings. In our comparative analysis, we explore to what degree European welfare states were capable to respond to this crisis by stabilizing employment and income for working people. While short-time work was a policy tool already partly used in the Great Recession, job retention policies were further expanded or newly introduced across Europe due to the pandemic in 2020. However, cross-national variations persist in the way in which these schemes were designed and implemented across European welfare states, aiming more or less towards labour hoarding to avoid mass dismissal throughout the employment crisis. We distinguish between business support and labour support logics in explaining the variation in job retention policies across Europe. Continental, Mediterranean and Liberal welfare states fostered more labour hoarding than Nordic or Central and Eastern European countries.